Challenges and coping strategies of visually impaired adults in Zeerust, South Africa - Tshuma, Cherpet; Ntombela, Ngenisiwe; Mabvurira, Vincent (Penerbit Universiti Kebangsaan Malaysia, 2021)
Despite efforts to reduce the adverse living conditions of people living with disabilities in South Africa, they continue to experience a myriad of challenges on a daily basis. The study aimed at exploring the challenges and coping strategies of Visually Impaired (VI) adults in Zeerust, South Africa. A qualitative research approach was adopted, and a descriptive (QD) design was used to collect data from fourteen participants with visual impairments. Purposive sampling and used to select participants and semi-structured interviews were used to collect data. Thematic content analysis and the Atlas Ti-version 8.4.23 software were used to analyse data. The results show that people with VI face different challenges such as unemployment, lack of privacy, illiteracy, stigmatization, accidental falls and isolation. To cope with such challenges, people with VI rely on support from family members, friends, social workers, nurses, and mobility instructors. Religion, self-acceptance, and addictive behaviours were also used as coping strategies. The study concludes that people with visual impairments in South Africa continue to face a number of challenges and efforts should be put in place to curb these challenges. Findings of this study may help relevant government departments and non-profit organisations working with people with disabilities to formulate appropriate policies and programmes. Community education remains crucial in creating conducive space for people with disabilities. Efforts should be put to continue providing life and vocational skills.